2016
DOI: 10.2147/dddt.s96818
|View full text |Cite
|
Sign up to set email alerts
|

YiQiFuMai powder injection ameliorates blood–brain barrier dysfunction and brain edema after focal cerebral ischemia–reperfusion injury in mice

Abstract: YiQiFuMai powder injection (YQFM) is a modern preparation derived from the traditional Chinese medicine Sheng-Mai-San. YQFM is widely used in clinical practice in the People’s Republic of China, mainly for the treatment of microcirculatory disturbance-related diseases. However, little is known about its role in animals with ischemic stroke. The aim of this study was to examine the effect of YQFM on brain edema and blood–brain barrier (BBB) dysfunction induced by cerebral ischemia–reperfusion (I/R) injury. Male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…We first investigated the effects of YQFM on rat cerebral I/R injury. We selected the dose (0.957 g/kg) from previous studies performed in mice but adjusted to rats [ 38 ]. According to the body surface area conversion, the dose of mice is about 1.4 times to rats; thus, 0.957 g/kg of YQFM was used in rats in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first investigated the effects of YQFM on rat cerebral I/R injury. We selected the dose (0.957 g/kg) from previous studies performed in mice but adjusted to rats [ 38 ]. According to the body surface area conversion, the dose of mice is about 1.4 times to rats; thus, 0.957 g/kg of YQFM was used in rats in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also indicated that YQFM protects against ischemic injury through regulating endoplasmic reticulum stress-mediated neuronal damage [ 36 ]. YQFM also ameliorates blood-brain barrier (BBB) dysfunction through NF- κ B and ROCK1/MLC signaling pathways [ 37 , 38 ]. More importantly, YQFM is effective in mitigating myocardial ischemia/reperfusion injury by modulating AMPK activation-mediated mitochondrial fission [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that Shengmai preparation, administered via injection or orally, and its active ingredients, Rb1 and ruscogenin, exert obvious protective effects against inflammation and BBB damage induced by ischemic brain injury. 16,19,49 However, the beneficial activity of GRS against ischemic stroke and associated mechanisms have not been established until now.…”
Section: Discussionmentioning
confidence: 99%
“…MCAO was induced in C57BL/6J mice, followed by reperfusion, as reported previously ( Figure 1B). 19 Mice were anesthetized with 4% chloral hydrate (0.1 mL per 10 g body weight, i.p.). Neck vessels were exposed by a midline incision, and the branches of the right external carotid artery carefully isolated and cauterized.…”
Section: Focal Cerebral I/rmentioning
confidence: 99%
“…Reperfusion after cerebral ischemia increases the risk of brain hemorrhage, while leading to neurovascular injury and producing excessive reactive oxygen species (ROS) which damage the blood-brain barrier (Alluri et al, 2015). A number of studies have confirmed that the disruption of the BBB is a major cause of the pathogenesis of ischemic stroke (Cao et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%